CARACTERIZAÇÃO TEMPORAL E ESPACIAL DA PRECIPITAÇÃO NO ENTORNO DO MUNICÍPIO DE SÃO GONÇALO (RJ) CONSIDERANDO A SÉRIE HISTÓRICA DE 1968 A 2002 - Carla Maciel Salgado; Tatiane da Cruz Silva; Gisele Cristina Augusto de Souza; Humberto Camelo de Freitas (Sociedade & Natureza)
The lack of urban planning and the environmental characteristics of São Gonçalo (RJ) makethis municipality vulnerable to floods. In order to contribute to actions that reduce this problem,this paper has the objective to characterize precipitation on a space and time perspective,using rain data of precipitation stations in São Gonçalo surroundings. The annual precipitationanalysis, considering the historic series (1968-2002), identified three different periods withrain variability: 1968-1980, 1981-1996 and 1997-2002. It was verified a rainnig spatialvariation using annual precipitation and frequency of rain classes. Regarding the precipitationstations near to the drainage basins that converge to São Gonçalo or that was in the municipality,it was verified a great water contribution to flood formation in the city.